MODEL PERLINDUNGAN HAK PEREMPUAN KORBAN TINDAK KEKERASAN DALAM RUMAH TANGGA - Arbaiyah Prantiasih; Moch Yuhdi; Siti Awaliyah (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2015)
accompanied by an increase in intensity and quality. The purpose of this study was: (1) describe theforms of violence that occur in women in the household, (2) describe the causes of women experiencingdomestic violence, (3) describe the form of the rights of women who experience violence, (4)describe the form of protection of the rights of women who experience domestic violence. This studyusing a design research. These results can be explained that: (1) forms of violence against women inthe household is physical violence, psychological violence and neglect, (2) the causes of occurrenceof physical violence because the husband is not working; husband husband’s job is erraticand temperamental, (3) the form of the rights of women subjected to violence to obtain protectionfrom KPPA, obtain an integrated service, get a guarantee of their rights whose status as a wife, as amother or as a child in the household, but it is not optimal to get, get assistance psychologically,medically, (4) the form of the protection of women victims of domestic violence, is providing assistance,providing services, provide a safe home means a temporary shelter for victims.Key words: violence, household, women